CORPORATE DIVIDEND POLICY AND SHARE PRICE VOLATILITY:A STUDY OF THE BOMBAY STOCK EXCHANGE - Vijayakumar, Arvind (2012)
Purpose: The research paper aims to identify the empirical relationship between Corporate Dividend policy in India and share price volatility.